Phonological Awareness and Word Reading Fluency Among Young Saudi Learners of English - Alzahrani, Asma; Algethami, Ghazi (International Journal of Language and Literary Studies, 2023)
The current study explored the relationship between phonological awareness and word reading fluency among young Saudi English as a Foreign Language (EFL)learners. Two tests were completed by thirty young Saudi EFL learners. The first test comprised 25 questions related to phonological awareness. In the second test, the learners were asked to read a list of English words in one minute, and each student was given a score based on how many words they read per minute. The students scored relatively low on both tests, indicatinga deficiency in phonological awareness and difficulty in word reading. The scores in both tests were significantly correlated, however, a regression analysis showed that only phonological awareness at the phonemic level was a significant predictor of the students’ performance in the word reading fluency test. The results clearly indicate that Saudi EFL learners could benefit from phonemic awareness training, and future studies should empirically examine its potentialfor improving Saudi EFL learners’ reading fluency.